Photoionization of atomic scandium in the ground state: Total cross sections and 3p -> 3d resonances - (:unkn) unknown (AMER PHYSICAL SOC, 1999)
A methodology is developed combining many-body-perturbation theory and close coupling of final-state channels with multiconfiguration Hartree-Fock theory to calculate photoionization cross sections of open-shell atoms with accurate threshold and resonance energies. Photoionization calculations of the ground 1s(2)2s(2)2p(6)3s(2)3p(6)3d4s(2) D state of atomic Sc, the first of the transition metals, are performed from threshold to 60 eV using this method. All single-electron transitions from 4s, 3d, and 3d subshells are included. Over a broad region of energy, the cross section is dominated by the strength of the 3p-->3d resonances which are split into nine distinct transitions through the angular momentum coupling with the open shells. The total cross section and the 3p-->3d resonances are presented in detail and reasonably good agreement with available experiment, for both energies and cross section, is obtained. Classifications of a number of the 3p-->3d resonances are proposed. In the low-energy region, good agreement with a previous R-matrix calculation is found. [S1050-2947(99)07505-8].
Keywords: METAL ATOMS